The Limnephilus bipunctatus Species Group in Turkey with the descriptions of two new species (Trichoptera, Limnephilidae) - Si̇pahi̇ler Füsun (Zootaxa, 2024)
The Limnephilus bipunctatus Species Group in Turkey is studied with two new species, Limnephilus bayburt sp. n. from northeastern Turkey and Limnephilus bercalan sp. n. from eastern Turkey, described and illustrated. Four additional species, L. bipunctatus Curtis 1834, L. caucasicus Schmid 1955, L. malickyi Sipahiler 1992, and L. transcaucasicus Martynov 1909 are also redescribed and illustrated. Limnephilus transcaucasicus is a new record for the Turkish fauna.